2004
DOI: 10.1158/1078-0432.ccr-03-0574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nuclear Factor-κB, Urokinase-Type Plasminogen Activator, and HBx and Their Clinicopathological Significance in Hepatocellular Carcinoma

Abstract: Purpose: Nuclear factor B (NF-B) signaling pathway is an important regulating pathway in human diseases and cancers. One of its downstream target genes is urokinase plasminogen activator (uPA), which is involved in cancer invasion and metastasis. The purpose of this study was to evaluate NF-B activation, uPA up-regulation, and hepatitis B viral X protein (HBx) expression in human hepatocellular carcinoma (HCC) and to assess their clinicopathological significance.Experimental Design: We evaluated NF-B activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…The first evidence implicating NF-B activation mediated pathogen-induced carcinogenesis was identification of the REV-T viral oncogene that causes avian reticuloendothelial lymphomatosis, v-Rel, which shares a Rel transactivation domain with the mammalian homologues NF-family members (47). Hepatitis B X protein and hepatitis C 5A and core proteins have been shown to activate NF-B and are implicated in carcinogenesis of hepatocellular carcinoma (48). In addition, the specific subtypes of human papillomavirus (HPV) infection are potentially oncogenic in the uterine cervix, vagina, vulva, anus, penis, skin, and oropharynx (49,50).…”
Section: Nf-b Links Inflammation To Cancermentioning
confidence: 99%
“…The first evidence implicating NF-B activation mediated pathogen-induced carcinogenesis was identification of the REV-T viral oncogene that causes avian reticuloendothelial lymphomatosis, v-Rel, which shares a Rel transactivation domain with the mammalian homologues NF-family members (47). Hepatitis B X protein and hepatitis C 5A and core proteins have been shown to activate NF-B and are implicated in carcinogenesis of hepatocellular carcinoma (48). In addition, the specific subtypes of human papillomavirus (HPV) infection are potentially oncogenic in the uterine cervix, vagina, vulva, anus, penis, skin, and oropharynx (49,50).…”
Section: Nf-b Links Inflammation To Cancermentioning
confidence: 99%
“…Furthermore, the oncogenic HBV protein HBx and the HCV core and NS5B proteins were reported to induce NF-B. [29][30][31] The natural conclusion from these observations was that NF-B operates as a tumor promoter in virus-infected or transformed hepatocytes.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 99%
“…Several in vitro studies utilizing human HCC cell lines have shown that NF-κB is cytoprotective by means of preventing apoptosis. In addition, the oncogenic HBV protein HBx and the HCV core were reported to induce NF-κB activation (Chan et al, 2004;Arsura and Cavin, 2005). Loss of NF-κB activity in parenchymal cells may actually promote tumor development.…”
Section: Hepatocellular Carcinoma and Nf-kbmentioning
confidence: 99%